A modified mini-incisional technique for double-eyelid blepharoplasty. Issue 2 (June 2016) - Hu, Xiaogen; Ma, Haihuan; Xue, Zhiqiang; Qi, Huijie; Chen, Bo; Zhou, Yang; Huang, Wengang
Background: Double-eyelid blepharoplasty is one of the most popular cosmetic surgeries in Asia. Objective: To introduce a modified mini-incisional technique to form a double eyelid. Methods: A total of 372 patients (325 women, 47 men) were involved in the study between July 2008 and August 2014. Their age ranged from 16 to 34 years, with a mean age of 24 years. All patients underwent the modified mini-incisional upper blepharoplasty. In the technique, four 2 mm incisions were made along the designed fold. The orbicularis muscle overlying the levator aponeurosis was removed. The removal of the lateral fat pad was completed accordingly. The medial fat pad was also removed if necessary. Suture was used to fix the skin to pretarsal fascia along the double-eyelid line. The double-eyelid crease was formed after the operation. Results: The follow-up period was three to 12 months (mean nine months). Most of the double eyelids were natural. During the follow-up period, 92% (342 of 372) patients were satisfied with the blepharoplasty. The most common complications were swelling within first week after the operation, which subsided spontaneously. Asymmetries occurred in 17 patients; six patients had multiple eyelids and seven patients experienced shifting of the fold. These were corrected six months after the operation. Disappearance of the fold was not observed. The scars of the stab incision became invisible after one full year of recovery. No other severe complications were found. Conclusion: The four mini-incisional blepharoplasty technique was successful for the formation of a natural-appearing and long-lasting double eyelid. Except for individuals with obvious skin redundancy, patients with a single eyelid are suitable candidates for the technique.